Ответ:
Задание 1
а) Ответ:
Объяснение:
б) Ответ:
Задание 2
Задание 3
Объяснение: 1) а) ⁵√8 ·√⁵(-4) +⁸√(-3)⁶= ⁵√-32 +⁴√3³ = -2+⁴√27
(плохо виден показатель третьего корня)
а) ⁵√8 ·√⁵(-4) +³√(-3)⁶= ⁵√-32 +3² = -2+9=7
б)⁹√6+√35 ·⁹√6-√35 = ⁹√(6+√35)·(6-√35)=⁹√36 -35 =⁹√1=1
2) а) 5/⁵√5 = ⁵√5⁴ б) 4/ (√3-1) = 4(√3+1) /(√3-1)(√3+1)= 4(√3+1)/ (3-1)= 4(√3+1)/2= 2(√√3+1);
3) а) ²⁰√а² - ⁵√√а = ¹⁰√а -¹⁰√а=0 б)2а·∛а⁴ · 3∛а²=6а·∛а⁶= 6а·а²=6а³
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
Задание 1
а) Ответ:![-2+\sqrt[4]{27} -2+\sqrt[4]{27}](https://tex.z-dn.net/?f=-2%2B%5Csqrt%5B4%5D%7B27%7D)
Объяснение:![\sqrt[5]{8} \sqrt[5]{-4} + \sqrt[8]{(-3)^6} = \sqrt[5]{8} *(-\sqrt[5]{4} ) + \sqrt[8]{3^6} = -\sqrt[5]{32} + \sqrt[4]{3^3} = -2 + \sqrt[4]{27} \sqrt[5]{8} \sqrt[5]{-4} + \sqrt[8]{(-3)^6} = \sqrt[5]{8} *(-\sqrt[5]{4} ) + \sqrt[8]{3^6} = -\sqrt[5]{32} + \sqrt[4]{3^3} = -2 + \sqrt[4]{27}](https://tex.z-dn.net/?f=%5Csqrt%5B5%5D%7B8%7D%20%5Csqrt%5B5%5D%7B-4%7D%20%2B%20%5Csqrt%5B8%5D%7B%28-3%29%5E6%7D%20%3D%20%5Csqrt%5B5%5D%7B8%7D%20%2A%28-%5Csqrt%5B5%5D%7B4%7D%20%29%20%2B%20%5Csqrt%5B8%5D%7B3%5E6%7D%20%3D%20-%5Csqrt%5B5%5D%7B32%7D%20%2B%20%5Csqrt%5B4%5D%7B3%5E3%7D%20%3D%20-2%20%2B%20%5Csqrt%5B4%5D%7B27%7D)
б) Ответ:![1 1](https://tex.z-dn.net/?f=1)
Объяснение:![\sqrt[6]{6+\sqrt{35} } * \sqrt[9]{6-\sqrt{35} } = \sqrt[9]{(6+\sqrt{35} *(6-\sqrt{35} )} = \sqrt[9]{36-35} = \sqrt[9]{1} =1 \sqrt[6]{6+\sqrt{35} } * \sqrt[9]{6-\sqrt{35} } = \sqrt[9]{(6+\sqrt{35} *(6-\sqrt{35} )} = \sqrt[9]{36-35} = \sqrt[9]{1} =1](https://tex.z-dn.net/?f=%5Csqrt%5B6%5D%7B6%2B%5Csqrt%7B35%7D%20%7D%20%2A%20%5Csqrt%5B9%5D%7B6-%5Csqrt%7B35%7D%20%7D%20%3D%20%5Csqrt%5B9%5D%7B%286%2B%5Csqrt%7B35%7D%20%2A%286-%5Csqrt%7B35%7D%20%29%7D%20%3D%20%5Csqrt%5B9%5D%7B36-35%7D%20%3D%20%5Csqrt%5B9%5D%7B1%7D%20%3D1)
Задание 2
а) Ответ:![\sqrt[5]{625} \sqrt[5]{625}](https://tex.z-dn.net/?f=%5Csqrt%5B5%5D%7B625%7D)
Объяснение:![\frac{5}{\sqrt[5]{5} } = \frac{5}{\sqrt[5]{5} } * \frac{\sqrt[5]{5^4} }{\sqrt[5]{5^4} } = \frac{5\sqrt[5]{5^4} }{\sqrt[5]{5} *\sqrt[5]{5^4} } = \frac{5\sqrt[5]{5^4} }{\sqrt[5]{5*5^4} } = \frac{5\sqrt[5]{5^4} }{\sqrt[5]{5^5} } = \frac{5\sqrt[5]{5^4} }{5} = \sqrt[5]{5^4} = \sqrt[5]{625} \frac{5}{\sqrt[5]{5} } = \frac{5}{\sqrt[5]{5} } * \frac{\sqrt[5]{5^4} }{\sqrt[5]{5^4} } = \frac{5\sqrt[5]{5^4} }{\sqrt[5]{5} *\sqrt[5]{5^4} } = \frac{5\sqrt[5]{5^4} }{\sqrt[5]{5*5^4} } = \frac{5\sqrt[5]{5^4} }{\sqrt[5]{5^5} } = \frac{5\sqrt[5]{5^4} }{5} = \sqrt[5]{5^4} = \sqrt[5]{625}](https://tex.z-dn.net/?f=%5Cfrac%7B5%7D%7B%5Csqrt%5B5%5D%7B5%7D%20%7D%20%3D%20%5Cfrac%7B5%7D%7B%5Csqrt%5B5%5D%7B5%7D%20%7D%20%2A%20%5Cfrac%7B%5Csqrt%5B5%5D%7B5%5E4%7D%20%7D%7B%5Csqrt%5B5%5D%7B5%5E4%7D%20%7D%20%3D%20%5Cfrac%7B5%5Csqrt%5B5%5D%7B5%5E4%7D%20%7D%7B%5Csqrt%5B5%5D%7B5%7D%20%2A%5Csqrt%5B5%5D%7B5%5E4%7D%20%7D%20%3D%20%5Cfrac%7B5%5Csqrt%5B5%5D%7B5%5E4%7D%20%7D%7B%5Csqrt%5B5%5D%7B5%2A5%5E4%7D%20%7D%20%3D%20%5Cfrac%7B5%5Csqrt%5B5%5D%7B5%5E4%7D%20%7D%7B%5Csqrt%5B5%5D%7B5%5E5%7D%20%7D%20%3D%20%5Cfrac%7B5%5Csqrt%5B5%5D%7B5%5E4%7D%20%7D%7B5%7D%20%3D%20%5Csqrt%5B5%5D%7B5%5E4%7D%20%3D%20%5Csqrt%5B5%5D%7B625%7D)
б) Ответ:![2\sqrt{3} +2 2\sqrt{3} +2](https://tex.z-dn.net/?f=2%5Csqrt%7B3%7D%20%2B2)
Объяснение:![\frac{4}{\sqrt{3}-1 } = \frac{4}{\sqrt{3}-1 } * \frac{\sqrt{3}+1 }{\sqrt{3}+1 } = \frac{4(\sqrt{3} +1)}{(\sqrt{3} -1)*(\sqrt{3}+1) } = \frac{4(\sqrt{3} +1)}{3-1} = \frac{4(\sqrt{3}+1 }{2} = 2(\sqrt{3} +1)= 2\sqrt{3} +2 \frac{4}{\sqrt{3}-1 } = \frac{4}{\sqrt{3}-1 } * \frac{\sqrt{3}+1 }{\sqrt{3}+1 } = \frac{4(\sqrt{3} +1)}{(\sqrt{3} -1)*(\sqrt{3}+1) } = \frac{4(\sqrt{3} +1)}{3-1} = \frac{4(\sqrt{3}+1 }{2} = 2(\sqrt{3} +1)= 2\sqrt{3} +2](https://tex.z-dn.net/?f=%5Cfrac%7B4%7D%7B%5Csqrt%7B3%7D-1%20%7D%20%3D%20%5Cfrac%7B4%7D%7B%5Csqrt%7B3%7D-1%20%7D%20%2A%20%5Cfrac%7B%5Csqrt%7B3%7D%2B1%20%7D%7B%5Csqrt%7B3%7D%2B1%20%7D%20%3D%20%5Cfrac%7B4%28%5Csqrt%7B3%7D%20%2B1%29%7D%7B%28%5Csqrt%7B3%7D%20-1%29%2A%28%5Csqrt%7B3%7D%2B1%29%20%7D%20%3D%20%5Cfrac%7B4%28%5Csqrt%7B3%7D%20%2B1%29%7D%7B3-1%7D%20%3D%20%5Cfrac%7B4%28%5Csqrt%7B3%7D%2B1%20%7D%7B2%7D%20%3D%202%28%5Csqrt%7B3%7D%20%2B1%29%3D%202%5Csqrt%7B3%7D%20%2B2)
Задание 3
а) Ответ:![0 0](https://tex.z-dn.net/?f=0)
Объяснение:![\sqrt[20]{a^2} -\sqrt[5]{\sqrt{a} } = \sqrt[10]{a} - \sqrt[10]{a} = 0 \sqrt[20]{a^2} -\sqrt[5]{\sqrt{a} } = \sqrt[10]{a} - \sqrt[10]{a} = 0](https://tex.z-dn.net/?f=%5Csqrt%5B20%5D%7Ba%5E2%7D%20-%5Csqrt%5B5%5D%7B%5Csqrt%7Ba%7D%20%7D%20%3D%20%5Csqrt%5B10%5D%7Ba%7D%20-%20%5Csqrt%5B10%5D%7Ba%7D%20%3D%200)
б) Ответ:![6a^3 6a^3](https://tex.z-dn.net/?f=6a%5E3)
Объяснение:![2a\sqrt[3]{a^4} * 3\sqrt[3]{a^2} = 2a\sqrt[3]{a^4*a^2} *3= 2a\sqrt[3]{a^6} *3= 2a*a^2*3=6a^3 2a\sqrt[3]{a^4} * 3\sqrt[3]{a^2} = 2a\sqrt[3]{a^4*a^2} *3= 2a\sqrt[3]{a^6} *3= 2a*a^2*3=6a^3](https://tex.z-dn.net/?f=2a%5Csqrt%5B3%5D%7Ba%5E4%7D%20%2A%203%5Csqrt%5B3%5D%7Ba%5E2%7D%20%3D%202a%5Csqrt%5B3%5D%7Ba%5E4%2Aa%5E2%7D%20%2A3%3D%202a%5Csqrt%5B3%5D%7Ba%5E6%7D%20%2A3%3D%202a%2Aa%5E2%2A3%3D6a%5E3)
Ответ:
Объяснение: 1) а) ⁵√8 ·√⁵(-4) +⁸√(-3)⁶= ⁵√-32 +⁴√3³ = -2+⁴√27
(плохо виден показатель третьего корня)
а) ⁵√8 ·√⁵(-4) +³√(-3)⁶= ⁵√-32 +3² = -2+9=7
б)⁹√6+√35 ·⁹√6-√35 = ⁹√(6+√35)·(6-√35)=⁹√36 -35 =⁹√1=1
2) а) 5/⁵√5 = ⁵√5⁴ б) 4/ (√3-1) = 4(√3+1) /(√3-1)(√3+1)= 4(√3+1)/ (3-1)= 4(√3+1)/2= 2(√√3+1);
3) а) ²⁰√а² - ⁵√√а = ¹⁰√а -¹⁰√а=0 б)2а·∛а⁴ · 3∛а²=6а·∛а⁶= 6а·а²=6а³